2021
DOI: 10.3390/agronomy11010103
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Trait Loci Mapping for Vigour and Survival Traits of Barley Seedlings after Germinating under Salinity Stress

Abstract: Seed germination and seedling establishment are the most critical stages in the barley (Hordeum vulgare ssp. vulgare L.) life cycle that contribute substantially to grain yield. These two phases are exposed to several forms of environmental stresses such as salinity due to high level of salt accumulation in the soil rhizosphere where seed germination takes place and seedlings emerge from. Previously, we have reported genotypic variability and independent QTLs associated with salinity tolerance at seedling and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 55 publications
6
15
1
Order By: Relevance
“…This result suggests that the phenotypic expression of one genotype that can be superior to another at the same salinity level, but inferior at the second level of salinity, and this consequently affects heritability estimates. Our findings agreed with other reports, where high heritability estimate values were observed under adverse conditions [35][36][37][38]. Many reports confirmed that the salt-tolerance index is a better selection tool for highly salt-tolerant and productive genotypes under salinity [13,37,38].…”
Section: Stress Tolerance Index and Heritabilitysupporting
confidence: 93%
See 2 more Smart Citations
“…This result suggests that the phenotypic expression of one genotype that can be superior to another at the same salinity level, but inferior at the second level of salinity, and this consequently affects heritability estimates. Our findings agreed with other reports, where high heritability estimate values were observed under adverse conditions [35][36][37][38]. Many reports confirmed that the salt-tolerance index is a better selection tool for highly salt-tolerant and productive genotypes under salinity [13,37,38].…”
Section: Stress Tolerance Index and Heritabilitysupporting
confidence: 93%
“…This finding suggests that these doubled haploid lines possess sufficient plasticity to respond to soil and water salinity constraints, as well as implying significant salt tolerance mechanisms. The results are in accordance with those obtained by Thabet et al [37] and Mwando et al [38]. On the other hand, twenty-six QTL were detected for the STI of the measured traits and covered the whole genome except chromosome 5H.…”
Section: Stress Tolerance Index and Heritabilitysupporting
confidence: 92%
See 1 more Smart Citation
“…Barley, the fourth most leading cereal crop worldwide, is one of the main winter cereals in the Mediterranean region [9]. Barley is relatively salt-tolerant and has the advantage of growing in marginal environments that are unsuitable for other cereal crops [9,10]. Therefore, it is oftentimes used as a model plant for understanding salinity adaptation mechanisms in crops and for studying the germination in monocots [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The adaptation of barley to salt stress differs from one growth stage to another, where the germination and the early development stages of plant growth are considered the most sensitive ones. Many studies investigated the effect of salt stress on barley seed germination and seedling development to determine the effect of salinity on plants and develop salt-tolerant accessions for breeding programs [10,13,14]. A clear reduction in germination percentage, rate, shoot length, root length, root fresh and dry weights, and relative growth rate was reported by increasing salinity levels in barley [10,[13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%